Investigation of the influence of temperature on the degradation mechanism of commercial nickel manganese cobalt oxide-type lithium-ion cells during long-term cycle tests. (February 2019) - Matsuda, Tomoyuki; Ando, Keisuke; Myojin, Masao; Matsumoto, Masashi; Sanada, Takashi; Takao, Naoki; Imai, Hideto; Imamura, Daichi
Highlights: Cycle degradation mechanism depends on test temperature. Electrolyte decomposition mainly causes degradation at high temperature. Surface amorphization of cathode occurs by the cycle test at room temperature. Charge-transfer resistance increases by surface amorphization. Abstract: The effect of temperature in long-term cycle tests was investigated using commercial nickel manganese cobalt oxide 18650-type lithium-ion cells, which were cycled at a current rate of 1C at 25 °C and 50 °C. The cell capacity decreased more rapidly at 50 °C than at 25 °C. Conversely, the internal resistance increased more rapidly at 25 °C than at 50 °C before increasing dramatically after ca. 700 cycles at 50 °C. Electrochemical impedance spectroscopy performed after the cycle tests revealed that the increase in ohmic resistance was larger at 50 °C, while the increase in charge-transfer resistance was larger at 25 °C. To elucidate the reasons for the differences in the degradation tendencies at different test temperatures, the electrochemical electrode properties, electrolyte compositions, and electrode materials were analyzed. The half-cell analyses showed that capacity fading was mainly caused by cell imbalances and cathode degradation at both test temperatures. 1 H and 19 F nuclear magnetic resonance spectroscopy revealed that the ohmic resistance increase at 50 °C was mainly due to decomposition of the electrolytes. X-ray photoelectron spectroscopy spectra indicated that the increase in charge-transfer resistance at 25 °C arose from the generation of high-valence Ni species on the cathode surface. Detailed analyses using hard X-ray photoelectron spectroscopy and transmission electron microscopy confirmed the existence of such Ni species only at the outermost layer as an amorphous phase. These results indicates that the degradation mechanism depends on temperature, and the appropriate control of temperature is important for prolonging the life of lithium-ion cells with nickel manganese cobalt oxide cathode.